Portafolio de inversiones y desempeño del sistema privado de pensiones peruano: 2000 – 2005 - Sanchez Cruz, David Juan (2009)
The present work is a vision of financial administration and portfolio management of Peruvian Private Pensions System (SPP), which takes like consumptions for the analyses to realize, the data that publishes the official supervisor. In search of the objectivity, we were sent, to the financial methodology, the official sources and the obtained results. We take as Theoretical Frame, the theory of Efficient Markets, the theory of the Portfolio, the Capital Assets Pricing Model (CAPM), the index Sharpe, Treynor, Jensen and Treynor-Mazuy.